Cell Adhesion on RGD-Displaying Knottins with Varying Numbers of Tryptophan Amino Acids to Tune the Affinity for Assembly on Cucurbit[8]uril Surfaces - Sankaran, Shrikrishnan (Langmuir, 2017)
[Image: see text] Cell adhesion is studied on multivalent knottins, displaying RGD ligands with a high affinity for integrin receptors, that are assembled on CB[8]-methylviologen-modified surfaces. The multivalency in the knottins stems from the number of tryptophan amino acid moieties, between 0 and 4, that can form a heteroternary complex with cucurbit[8]uril (CB[8]) and surface-tethered methylviologen (MV(2+)). The binding affinity of the knottins with CB[8] and MV(2+) surfaces was evaluated using surface plasmon resonance spectroscopy. Specific binding occurred, and the affinity increased with the valency of tryptophans on the knottin. Additionally, increased multilayer formation was observed, attributed to homoternary complex formation between tryptophan residues of different knottins and CB[8]. Thus, we were able to control the surface coverage of the knottins by valency and concentration. Cell experiments with mouse myoblast (C2C12) cells on the self-assembled knottin surfaces showed specific integrin recognition by the RGD-displaying knottins. Moreover, cells were observed to elongate more on the supramolecular knottin surfaces with a higher valency, and in addition, more pronounced focal adhesion formation was observed on the higher-valency knottin surfaces. We attribute this effect to the enhanced coverage and the enhanced affinity of the knottins in their interaction with the CB[8] surface. Collectively, these results are promising for the development of biomaterials including knottins via CB[8] ternary complexes for tunable interactions with cells.